PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN PEMBERIAN BANTUAN HUKUM KEPADA KLIEN OLEH ADVOKAT DALAM PERKARA PERDATA - Gede Arya Eka Candra (Jurnal Komunikasi Hukum, 2025)
This study aims to comprehensively describe how the role of information technology can improve the quality, effectiveness, and efficiency of legal aid provision by advocates to clients in civil cases. The advancement of digital technology has had a major impact on various sectors of life, including the legal field. In the civil context, advocates are not only required to understand the substantive legal aspects, but must also be able to utilize information technology to answer the complexity of resolving cases quickly and accurately. This study uses a juridical-empirical approach with a qualitative descriptive nature. Data were collected through literature studies, observations, and interviews with advocates and other stakeholders.The results of the study show that the use of information technology, such as the e-Court system, online legal databases, case management software, and digital communication media, has made it easier for advocates to carry out their professional duties, from drafting lawsuits, legal consultations, to conducting online trials. This technology has been proven to save time, costs, and expand the reach of legal services, especially for clients who are far from legal centers or who have limited mobility. However, the use of technology in legal practice also faces a number of challenges, such as the digital divide, limited infrastructure, low technological literacy among regional advocates, and concerns about data security and the confidentiality of legal information. Therefore, support is needed from the government, professional organizations, and legal education institutions in the form of training, adaptive regulations, and the provision of equitable access to technology. With these efforts, it is hoped that the use of information technology in legal aid practices can be a means to strengthen access to justice in a more inclusive and sustainable manner.